Design and Development of A Four Legged Robotic Horse - Chutia, R; Sharma, S; Kaushik, R; Tasa, B.P (International Journal of Computer Sciences and Engineering, 2019)
n this world, where human beings and the other animals have access to every nook and corner, the existing wheeled vehicles are far behind. In this paper we present the design and development of a four legged walking robotic horse. The main vision of our work is to represent the four legged robotic horse prototype that can serve in much larger range of environment and most difficult terrain, where the wheeled vehicle fails. The design of the robotic horse is bio inspired and is analogous to the biological horse. Prior to the development of the quadruped robot, the gait pattern of a horse with walk, trot and gallop styles are analyzed. A robotic prototype with gait patterns walk, trot and gallop similar to its biological counterpart, has been developed which is actuated by servomotors and controlled by microcontrollers. This paper presents the various analysis of the gait patters and development of the robotic prototype.